2022
DOI: 10.3390/batteries9010009
|View full text |Cite
|
Sign up to set email alerts
|

Particle Contamination in Commercial Lithium-Ion Cells—Risk Assessment with Focus on Internal Short Circuits and Replication by Currently Discussed Trigger Methods

Abstract: A possible contamination with impurities or material weak points generated in cell production of lithium-ion batteries increases the risk of spontaneous internal short circuits (ISC). An ISC can lead to a sudden thermal runaway (TR) of the cell, thereby making these faults especially dangerous. Evaluation regarding the criticality of an ISC, the development of detection methods for timely fault warning and possible protection concepts require a realistic failure replication for general validation. Various trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 89 publications
(168 reference statements)
0
8
0
Order By: Relevance
“…Based on the diaphragm failure mechanism and various abuse conditions, ISC faults in lithium battery packs can be classified into three primary types: (1) mechanical abuse-induced ISC; (2) electrical abuse-induced ISC; and (3) thermal abuse-induced ISC. ISC resulting from mechanical or thermal abuse tends to rapidly generate significant heat, often leading directly to thermal runaway [35]. Conversely, ISC triggered by electrical abuse typically generates less heat that is insufficient to provoke thermal runaway.…”
Section: Isc Fault Triggering Mechanismmentioning
confidence: 99%
“…Based on the diaphragm failure mechanism and various abuse conditions, ISC faults in lithium battery packs can be classified into three primary types: (1) mechanical abuse-induced ISC; (2) electrical abuse-induced ISC; and (3) thermal abuse-induced ISC. ISC resulting from mechanical or thermal abuse tends to rapidly generate significant heat, often leading directly to thermal runaway [35]. Conversely, ISC triggered by electrical abuse typically generates less heat that is insufficient to provoke thermal runaway.…”
Section: Isc Fault Triggering Mechanismmentioning
confidence: 99%
“…It has been reported that lithium-ion batteries can fail due to variances in the concentration of electrolytes as well as due to the introduction of contaminants. 48 The workshop presents the students with the problem of identifying why and how the battery malfunctioned, through a guided "electro-analytical" workshop consisting of two major parts: (1) a quantitative section and…”
Section: Narrativementioning
confidence: 99%
“…Aluminum, copper, and iron are some of the most common contaminants in lithium-ion battery electrolytes, since all three are already present within batteries. 48 A qualitative test for aluminum, copper, and iron cations involves the use of NaOH to produce the equivalent metal hydroxides, which results in the formation of a precipitate. Iron(III) forms a yellowishbrownish precipitate; copper(II) forms a blue precipitate, and aluminum(III) forms a white precipitate (Figure 3).…”
Section: Qualitativementioning
confidence: 99%
See 1 more Smart Citation
“…17 Although many ISC triggering methods have been developed, some of which have been adopted by industrial standards, 7,18 each method has advantages and disadvantages. 19 For example, nail penetration testing, pinch-testing, indentation testing and laser heating can be implemented without modification of Li-ion cells, but these methods cannot control the types of ISC. Embedding a nickel particle can control the types of ISC, but it requires disassembly of fully charged Li-ion cells which is difficult and dangerous.…”
Section: Introductionmentioning
confidence: 99%